تحسين نسبة إنبات بذور شجيرات الرغل الأمريكي Atriplex canescens (Pursh.)Nutt. - محمد, ياسين (Latakia University Journal -Biological Sciences Series, 2018)
جُمعت ثمار شجيرات الرغل الأمريكي Atriplex canescens (Pursh.)Nutt. من موقعين مختلفين بيئيا، الموقع الأول داخلي والثاني ساحلي، وذلك بهدف تحسين نسبة إنباتها بمعاملتها بطرق مختلفة قبل زراعتها في المشاتل الرعوية, واختبار إمكانية الاعتماد على ثمار ساحلية المصدر في إنتاج كميات كبيرة من شتول الرغل الأمريكي . نُفذت التجارب على 1600 ثمرة، قُسمت إلى أربع مجموعات, واستُخدمت في أربع تجارب مخبرية هي: تجربة الشاهد وثمارها داخلية المصدر دون أية معاملة- تجربة الثمار ساحلية المصدر دون أية معاملة- تجربة المعاملة بالخدش الميكانيكي - تجربة المعاملة بحمض الكبريت المركز التجاري لمدة ثانية واحدة . أظهرت نتائج الدراسة انخفاض متوسط نسبة إنتاش بذور الرغل الأمريكي ساحلية المصدر إلى 7.75% مقارنة بداخلية المصدر (الشاهد) والبالغ 17%. كما أظهرت نجاح طريقة المعاملة بالخدش الميكانيكي وتفوقها في رفع نسبة إنتاش بذور الرغل الأمريكي إلى 68.5 % وتنظيم الإنتاش وتسريعه . Seeds of fourwing saltbush atriplex canescens (Pursh.) Nutt. were collected from two sites, having different ecological conditions: the first is inland, the second is coastal. The aim is to study the possibility of using coastal seeds for the production of a lot of seedling of fourwing saltbush in order to improve seed germination. The experiments were applied to 1600 seeds, which were divided into four groups: control with inland seeds without any treatment; experiment with coastal seeds without any treatment; mechanical treatment; and treatment with concentrated sulphuric acid (H2SO4) for one second. Results showed a reduction in the proportion of germination of coastal seeds, in comparison with control, from 17% to 7.75%. Mechanical treatment was the best for acceleration and regulation of germination and for raising the percentage, in comparison with control, from 17% to 68.5%.